2020
DOI: 10.1186/s12906-020-02897-5
|View full text |Cite
|
Sign up to set email alerts
|

Water extract from processed Polygonum multiflorum modulate gut microbiota and glucose metabolism on insulin resistant rats

Abstract: Background: The incidence of insulin resistance (IR) has rapidly increased worldwide over the last 20 years, no perfect solution has yet been identified. Finding new therapeutic drugs will help improve this situation. As a traditional Chinese medicine, PPM (processed Polygonum multiflorum) has widely been used in the clinic. Recently, other clinical functions of PPM have been widely analyzed. Results: Administration of the water extract from PPM decreased the level of FBG, TC, and TG, and increased the level o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…TGF-β1 derived from dermal papillae cells inhibits hair growth and initiates catagen. 14–16 It promotes fibrosis by the Smad pathway 17–19 and is upregulated under various fibroproliferative conditions. 4 , 20 The genes encoding TGF-β were upregulated in CCCA tissue compared with non-involved tissues of the same patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TGF-β1 derived from dermal papillae cells inhibits hair growth and initiates catagen. 14–16 It promotes fibrosis by the Smad pathway 17–19 and is upregulated under various fibroproliferative conditions. 4 , 20 The genes encoding TGF-β were upregulated in CCCA tissue compared with non-involved tissues of the same patient.…”
Section: Discussionmentioning
confidence: 99%
“…Antifibrotic properties, that is, it activates AMPK through 4-hydroxyisoleucine and upregulates PPAR-γ protein expression 22–24 2. Major steroidal sapogenin in the fenugreek seed, diosgenin, demonstrates several anti-inflammatory functions, such as reduction in the production of inflammatory mediators in macrophages and counteracting the effects of proinflammatory cytokines, such as IL-6 and TNF- α ; 19 , 28 and promotion of angiogenesis and vasodilation with improved blood flow to the scalp and increased supply of nutrients to the hair follicles 29 Fo-ti extract Polygonum multiflorum root extract Exhibits antifibrotic properties, that is, the upregulation of the AMPK pathway 17 , 30 and activation of the PPAR-γ transcription through its anthraquinone moiety. 31 Abbreviations : CCCA, central centrifugal cicatricial alopecia; INCI, International Nomenclature Cosmetic Ingredient; TGF-β, transforming growth factor-beta; AMPK, AMP-activated protein kinase; COX-2, cyclooxygenase-2; THC, tetrahydrocurcumin; PPAR-γ, peroxisome proliferator-activated receptor gamma; NF-κB, nuclear factor kappa B; iNOS, nitric oxide synthase; TNF-α, tumor necrosis factor alpha; IL, interleukin; MCP, monocyte chemoattractant protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the studies on the gut microbiome, Ryu et al [25] reported the role and function of gut microbes from a pediatric point of view, with a focus on gut microbes and oriental medicine research. Experimental studies have analyzed the role of intestinal microbes in metabolic diseases, related to the intestine, such as diabetes [26][27][28][29], obesity [30][31][32][33], irritable bowel syndrome [34,35], and intestinal inflammatory diseases [36,37]. Several studies have also analyzed the effect of herbal medicines on the imbalance of intestinal microflora caused by antibiotics [16][17][18][19], but they are limited to some prescriptions and individual drugs and have not been reported in Korea.…”
Section: Discussionmentioning
confidence: 99%
“…The dry roots of Polygonum multiflorum (PM), as a natural tonic and traditional Chinese medicine (TCM), 1,2 have extensive biological activities and clinical effects, such as anti-tumour, 3,4 antiinflammation, 5,6 anti-ageing and anti-apoptosis, 7 antioxidant activity, [8][9][10] anti-hyperlipidaemia, 11 antibacterial, 12 and relieving insulin resistance. 13,14 Meanwhile, PM can detoxify, nourish liver and kidney, 15 and strengthen both muscles and bones in TCM theory. 16 In clinical practice, PM is frequently used for treating many diseases including constipation, hypertension, 17 and premature greying of hair.…”
Section: Introductionmentioning
confidence: 99%